Music and neuro-cognitive deficits in depression - Raghavendra, Prathima A.; Hegde, Shantala; Philip, Mariamma; Kesavan, Muralidharan (Frontiers in Psychology, 2022)
Abstract Background: Cognitive deficits are one of the core features of major depressive disorder (MDD) that play crucial role in functional recovery. Studies have explored cognitive deficits in MDD however given inconsistent results, especially in mild-moderate MDD. Recently, studies have explored music as cognitive ability in various clinical conditions. In MDD, large focus has been on evaluating emotion deficits and just a handful on music cognition. With growing evidence on use of music based intervention to target cognitive deficits, it is imperative to explore nature of music cognitive ability in MDD. Aim: To examine Musical and Neuro-cognitive deficits in patients with mild-moderate major depressive disorder (MDD) Method: Patients diagnosed with mild or moderate MDD (n=19) and matched healthy controls (HC) (n=18) were evaluated on selected tests from NIMHANS Neuropsychological test battery and Montreal battery for evaluation of amusia. Results: MDD group performed significantly lower than HC on working memory (p=0.007), verbal learning (p=0.02) and retention (p=0.03). Three indices were computed for a comprehensive evaluation. Groups did not differ significantly in any of the indices- focussed attention, executive function, learning and memory as well as on music cognition. Focussed attention and memory index predicted music cognition in HC and the combined group (MDD+HC) (p<0.01). Attention alone contributed to 62.1% of variance in music cognition. Similarly, music cognition significantly predicted focused attention (p<0.01) Conclusion: Individuals with mild-moderate MDD show significant deficits in working memory, verbal learning and memory however, not in music cognition. There exists a significant relationship between music cognition and attention, which could be implicated in use of music interventions to ameliorate cognitive deficits. Limitations of study include small sample size and heterogeneity. Future studies on larger cohort examining musical emotion and neurocognition is imperative to have deeper understanding of this debilitating condition.